Exploring Competency Confusion among Islamic Banking Students in Relation to the Alignment of Course Materials with Workplace Requirements - Edi Nur Prasetyo; Millatul Fadhilah (LifeSciFi, 2026)
A mismatch between Islamic Banking education and workplace requirements may contribute to competency confusion among students. This study aims to explore students’ perceptions of the alignment between course materials and workplace requirements and their relationship with competency confusion among Islamic Banking students. Using a qualitative approach, data were collected through in-depth interviews and analyzed thematically to identify students’ perceptions of the relevance of course content to workplace expectations. The findings reveal that most respondents experienced competency confusion due to a perceived mismatch between course materials and the realities of the Islamic banking industry. In contrast, some students viewed the curriculum as relatively aligned with workplace demands and demonstrated clearer career orientations. A smaller group expressed uncertainty, largely influenced by low motivation and unclear career goals. The results indicate that the misalignment between academic learning and workplace realities contributes to competency confusion among Islamic Banking students, highlighting the need for a more practice-oriented curriculum. This study contributes to the development of Islamic Banking education by providing insights for curriculum improvement to better align graduate competencies with industry needs.